2020
DOI: 10.1111/ffe.13376
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic and stochastic approach to fatigue crack nucleation in coarse grain RR1000 using local stored energy

Abstract: The crystal plasticity finite element (CPFE) method is used in conjunction with a critical local stored energy criterion to predict crack nucleation life for Coarse Grain (CG) nickel superalloy RR1000. Artificial representative microstructures are generated using Dream3D, and through simulation of multiple microstructural instantiations, a distribution of simulated fatigue response is generated. Fatigue of CG RR1000 is studied at 300°C and 700°C and at two R ratios of R = 0.1 and R = −1 giving a range of condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…[1][2][3] Especially in recent days, the concept of very-high-cycle fatigue (VHCF) with over 10 7 cycles fatigue life has been widely concerned, and a series of research results have been obtained. [4][5][6] However, most of the experimental studies are limited to room temperature, and the S-N characteristics, 7-13 failure mechanism, [14][15][16][17][18][19][20][21][22][23][24] and fatigue life evaluation methods [25][26][27][28][29][30][31][32] under elevated temperature environment in VHCF regime are not yet well understood. Therefore, in order to ensure the long-term safety of structural components, the VHCF fatigue characteristics of structural materials in elevated temperature environment still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Especially in recent days, the concept of very-high-cycle fatigue (VHCF) with over 10 7 cycles fatigue life has been widely concerned, and a series of research results have been obtained. [4][5][6] However, most of the experimental studies are limited to room temperature, and the S-N characteristics, 7-13 failure mechanism, [14][15][16][17][18][19][20][21][22][23][24] and fatigue life evaluation methods [25][26][27][28][29][30][31][32] under elevated temperature environment in VHCF regime are not yet well understood. Therefore, in order to ensure the long-term safety of structural components, the VHCF fatigue characteristics of structural materials in elevated temperature environment still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Okazaki et al 28 showed the relationship between range of defect sizes and fatigue limit. Pan et al 29 combined the crystal plasticity finite element method and a critical local stored energy criterion to predict crack nucleation life. Moreover, Steuer et al, 30 Cervellon et al, 31 and some other scholars 32,34 established fatigue indicator parameter method to predict the fatigue life of Ni-based superalloy with defect size, Schmidt factor, and elastic modulus.…”
Section: Introductionmentioning
confidence: 99%